Elements of success: Olympic swimming gold medalists' understanding of their competition-day routines - Grant, M. A.; Schempp, P. (International Journal of Sports Science and Coaching, 2014)
This study examined the competitive routines that five male Olympic gold medalist swimmers from the 2008 Beijing Summer Olympic Games undertook during successful elite competition days that they believe were critical to their success. Researchers sought to understand the significance of these actions based upon the meaning provided by these elite athletes. Participants engaged in an initial interview, a two-day training visit, a competition observation during an elite meet, and a follow-up interview. The swimmers' coaches were interviewed as key informants. Utilizing constructivist grounded theory, the larger study yielded several key results. First, researchers detailed a new holistic competition-day routine consisting of 12 segments and 2 types of preparations. Second, the purpose of this article was to define four elements that were critical to the athletes understanding and adherence to their competition-day routine. Each of the elements, which were flexibility, adaptation, time management, and task acquisition, was significant both individually and collectively.